Strategi Pengembangan Program Supervisi Akademik Berbasis Coaching untuk Meningkatkan Mutu Pembelajaran di Sekolah Menengah - Sugiyanto, Febri; Wati, Sartina (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to formulate a strategy for developing an educational supervision program based on a systematic and sustainable approach to improve the quality of learning. This research uses a qualitative approach with a library research method by analyzing relevant literature from journals, books, and scientific reports. The data were analyzed using content analysis techniques to identify key patterns and strategies in supervision practices. The results show that effective supervision program development consists of four main stages: (1) identification of supervision needs, (2) formulation of supervision strategies, (3) selection of appropriate supervision techniques, and (4) implementation and evaluation. In addition, the integration of coaching-based supervision, technology utilization, and collaborative approaches significantly contributes to improving teacher professionalism and learning quality. This study implies that supervision programs should be designed contextually, data-driven, and oriented toward continuous professional development.